2004
DOI: 10.1016/j.amjhyper.2004.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase inhibition accelerates the pressor response to low-dose angiotensin II, exacerbates target organ damage, and induces renin escape

Abstract: Because nitric oxide may attenuate both the pressor and cytotoxic effects of angiotensin II (Ang II), we investigated whether nitric oxide synthase (NOS) inhibition might accelerate the slow pressor effect of Ang II, and augment target organ damage. Using conscious, chronically catheterized rats, we previously observed that low-dose Ang II (10 ng/kg/min) rapidly increased mean arterial pressure (MAP) by approximately 25 mm Hg. The MAP then remained at this level for 2 to 4 days, and then increased again during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Thus we can only suggest a defective autoregulatory response to the fall in blood pressure in Sham and ANG IIϩMMF groups, since TGF is the main component of the autoregulatory response. In addition, it should be recognized that while our results suggest that renal ANG II is responsible for the glomerular hemodynamic findings in the salt-driven hypertension that follows exogenous angiotensin administration, the potential role of incomplete suppression of circulating angiotensin levels (12) was not addressed in this investigation.…”
Section: Effects Of Candesartan On Renal Hemodynamicsmentioning
confidence: 67%
“…Thus we can only suggest a defective autoregulatory response to the fall in blood pressure in Sham and ANG IIϩMMF groups, since TGF is the main component of the autoregulatory response. In addition, it should be recognized that while our results suggest that renal ANG II is responsible for the glomerular hemodynamic findings in the salt-driven hypertension that follows exogenous angiotensin administration, the potential role of incomplete suppression of circulating angiotensin levels (12) was not addressed in this investigation.…”
Section: Effects Of Candesartan On Renal Hemodynamicsmentioning
confidence: 67%
“…Although not an extensively studied model of hypertension, previous groups have investigated the chronic effects of ANG IIϩL-NAME administration on renal injury. Hu et al (13) demonstrated that the administration of pressor doses of L-NAME (10 g·kg Ϫ1 ·min Ϫ1 ) in combination with a small dose of ANG II (10 ng· kg Ϫ1 ·min Ϫ1 ) in rats exacerbated both the hypertension and renal injury compared with rats made hypertensive with L-NAME or ANG II alone; however, the magnitude of BP-dependent vs. BPindependent renal injury was not determined. Particularly relevant to the results of our study, Henke et al (12) reported that suppression of endothelial NF-B, a master regulatory transcription factor influencing several potential pathways of injury (i.e., oxidative stress, inflammation, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ANG II, renin may have direct effects to increase proteinuria in CKD, acting through the (pro)rennin receptor (48). Interestingly, the combination of enalapril and paricalcitol showed a larger decrease in renal glomerulosclerosis in experimental CKD, possibly by decreasing TGF-␤ expression and macrophage infiltration (ED1 positive) (78).…”
Section: Role Of Vdra In Proteinuriamentioning
confidence: 99%